Correlation studies for drought tolerance in Indian mustard (Brassica juncea) under different water regimes - MONIKA, MONIKA; YADAV, RAM C; YADAV, NEELAM R; KUMAR, NAVEEN; AVTAR, RAM; SINGH, DHIRAJ (The Indian Journal of Agricultural Sciences, 2020)
Indian mustard (Brassica juncea (L.) Czern & Coss) is the major oilseed crop of India ranking first both in acreage and production of rapeseed and mustard in Asia. Among abiotic stresses, drought condition may cause the most fatal economic losses in agriculture due to their wide range occurrence. Present investigation was undertaken with the objective to study RB 50 Ã— Kranti F2:3 population under irrigated and drought environments for phenotypic and genetic variability, broad-sense heritability, and interrelationships among agronomic and seed quality traits to select Indian mustard genotypes for drought tolerance in research area of oilseed section. The study was carried out at CCS Haryana Agricultural University, Hisar during rabi 2014-15. Higher mean values for agronomic traits were observed under irrigated than drought environment. Phenotypic correlation coefficient analysis of F2:3 populations under irrigated conditions was calculated to assess the association between various traits. Fifty three promising plants with higher seed yield as well as better physiological traits having greater drought tolerance were selected, which may be useful material for further studies and cultivar development for drought tolerance.